Nusinersen in adults with 5q spinal muscular atrophy: a non-interventional, multicentre, observational cohort study - Hagenacker, Tim; Weiler, Markus; Ziegler, Andreas (The lancet, 2020)
Background - Nusinersen is approved for the treatment of 5q spinal muscular atrophy of all types and stages in patients of all ages. Although clinical trials have shown improvements in motor function in infants and children treated with the drug, data for adults are scarce. We aimed to assess the safety and efficacy of nusinersen in adults with 5q spinal muscular atrophy. - Methods - We did an observational cohort study at ten academic clinical sites in Germany. Patients with genetically confirmed 5q spinal muscular atrophy (age 16-65 years) with a homozygous deletion of exons 7, 8, or both, or with compound heterozygous mutations were eligible for inclusion and received nusinersen treatment in accordance with the label for a minimum treatment time of 6 months to a follow-up of up to 14 months. The primary outcome was the change in the total Hammersmith Functional Motor Scale Expanded (HFMSE) score, assessed at months 6, 10, and 14, and based on pre-post comparisons. This study is registered with the German Clinical Trials Register (number DRKS00015702). - Findings - Between July 13, 2017, and May 1, 2019, 173 patients were screened, of whom 139 (80%) were eligible for data analysis. Of these, 124 (89%) were included in the 6-month analysis, 92 (66%) in the 10-month analysis, and 57 (41%) in the 14-month analysis; patients with missing baseline HFMSE scores were excluded from these analyses. Mean HFMSE scores were significantly increased compared with baseline at 6 months (mean difference 1·73 [95% CI 1·05-2·41], p<0·0001), 10 months (2·58 [1·76-3·39], p<0·0001), and 14 months (3·12 [2·06-4·19], p<0·0001). Clinically meaningful improvements (≥3 points increase) in HFMSE scores were seen in 35 (28%) of 124 patients at 6 months, 33 (35%) of 92 at 10 months, and 23 (40%) of 57 at 14 months. To 14-month follow-up, the most frequent adverse effects among 173 patients were headache (61 [35%] patients), back pain (38 [22%]), and nausea (19 [11%]). No serious adverse events were reported. - Interpretation - Despite the limitations of the observational study design and a slow functional decline throughout the natural disease course, our data provide evidence for the safety and efficacy of nusinersen in the treatment of adults with 5q spinal muscular atrophy, with clinically meaningful improvements in motor function in a real-world cohort. - Funding - None.
Gesehen am 04.05.2020